Role of insulin resistance and hyperinsulinemia in cardiovascular disease - Ahmad H. Asdie Ahmad H. Asdie (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1993)
Resi,stance to insulin-stimulated glucose uptake is present in the great majority of patients with impaired glucose tolerance or type 2 diabetes mellitus, in first degree relatives of patients with type 2 diabetes mellitus, as well as in approximately 25% of non-obese individuals with normal oral glucose tolerance. Deterioration of glucose tolerance can be prevented if beta cell is able to produce more insulin resulting hyperinsulinemia.The association between hypertension and diabetes mellitus is well recognized. Several reasons for the coexistence of these disorders have been postulated, i.e. as part of aging process, diabetes causes macrovascular and microvascular disease, renovascular stenosis which is enhanced by the development of hypertension. Insulin causes renal sodium reabsorption, stimulates the sympathetic nervous system, increases intracellular calcium, and is a vascular growth factor.Insulin resistance, hyperinsulinemia, impaired glucose tolerance, increased plasma triglyceride, and decreased HDL-cholesterol concentration have been shown to be associated with increased risk of coronary heart disease. Based upon these considerations, it raised the possibility that insulin resistance and hyperinsulinemia are involved in the etiology and clinical course of three major related disease; the type 2 diabetes mellitus, hypertension, and coronary heart disease.Key Words: hyperinsulinemia insulin resistance cardiovascular disease glucose homeostasis aging